Andere Blicke Religion und visuelle Kulturen auf dem Balkan und im Nahen Osten - Kaser, Karl (2013)
The 'pictorial turn' has had significant impact on the human, cultural, religious and social sciences since the middle of the 1990s; theory construction has been primarily oriented towards the western world. This is why one of the primary aims of this volume is the enlargement of theory construction by a different point of view - the Balkan and the Near Eastern one. The central research question of the thesis is that photography opened the door to the visual culture of the West.